Evaluating the Breed and Production Diversity in Dual Purpose Cattle Systems in Colombia: Opportunities for Its Sustainability - Burgos Paz, William; Pérez Escobar, Yury; Castillo Losada, Eduardo; Rivera Sanchez, Leidy; Falla Tapias, Sergio (Multidisciplinary Digital Publishing Institute - MDPI, 2025)
Approximately 60% of milk production in Colombia comes from dual-purpose (DP) systems, which face limitations in defining racial composition and maintaining production records for genetic resource management in the regions. The objective of this study was to evaluate the phenotypic diversity of cattle in DP systems and generate indicators that link this diversity to productivity, contributing to sustainability in these territories. A total of 2760 animals were phenotypically classified using two criteria associated with Breed Classification (BC) and Apparent Phenotypic Predominance (APP). Linear mixed models including fixed effects of region, covariates of age of cow and days in milk, and animal as random effect, were applied to daily milk records from 2042 cows to estimate the productivity of the breed assignment criteria in the genetic resource management. Most animals (66.92%) were assigned to the Mixed genetic group because its unknown genetic origin. Based on BC the second group comprise individuals classified as Crossbred (10.72%) that exhibit known genetic origin, but their genetic management was hindered by the lack of productive information. Meanwhile, the APP criteria was relevant to describe how either zebuine or taurine breed predominance influenced the daily milk production (3.52 ± 0.76 to 5.8 ± 0.14 kg, respectively) of individuals according to the environmental offerings in the regions. When assessing the impact of phenotypic selection processes in females based on a 1 kg increase in daily milk production could raise the population’s average daily productivity by 0.49 kg. However, this approach poses a risk to the inventory of Mixed animals, which have been used as a genetic resource adapted to the region for several decades.